2010
DOI: 10.1177/1933719109359704
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Oxidative Stress and Antioxidant Status in Women With Uncomplicated Pregnancies Throughout Gestation

Abstract: Pregnancy is associated with increased oxidative stress, and exaggeration of oxidative damage is considered important in pregnancy complications such as preeclampsia. There is, however, only scattered information regarding the longitudinal change of oxidative stress during pregnancy. We surmised that the placenta is the cause of the increased oxidative stress during pregnancy and hypothesized that the amount of placenta-derived cell-free fetal DNA in maternal plasma is correlated with maternal oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 38 publications
7
68
2
2
Order By: Relevance
“…Data from these independent cohorts suggest a 40% increase in 8-iso-PGF 2α levels at the end of pregnancy. However, it was previously shown that plasma 8-iso-PGF 2α levels are significantly increased by about two-fold from 15-20 weeks to the 37-41 weeks of pregnancy [52]. In the present study, levels of the various F 2 -isoPs varied from 0 (iPF 2α -IV) to 2.4-fold (iPF 2α -VI + 5-iPF 2α -VI) at the end of pregnancy compared to early pregnancy.…”
Section: Discussionmentioning
confidence: 61%
“…Data from these independent cohorts suggest a 40% increase in 8-iso-PGF 2α levels at the end of pregnancy. However, it was previously shown that plasma 8-iso-PGF 2α levels are significantly increased by about two-fold from 15-20 weeks to the 37-41 weeks of pregnancy [52]. In the present study, levels of the various F 2 -isoPs varied from 0 (iPF 2α -IV) to 2.4-fold (iPF 2α -VI + 5-iPF 2α -VI) at the end of pregnancy compared to early pregnancy.…”
Section: Discussionmentioning
confidence: 61%
“…Another cause of deficiency of these antioxidants during pregnancy could be placental transfer. Significant changes in the antioxidant enzyme activities have also been observed in pregnant females (Watson et al 1997, Djordjevic et al 2004, Jauniaux et al 2005, Oztabak et al 2005, Erisir et al 2009, Hung et al 2010.…”
Section: Discussionmentioning
confidence: 91%
“…As pregnancy and fetal growth progress, an overproduction of ROS in placental and fetal mitochondria is observed (Kim et al 2005). It is thought that the placenta is a major source of oxidative stress in pregnant females (Gitto et al 2002, Myatt and Cui 2004, Hung et al 2010. A significant part of the total indicators of pregnancy-related oxidative stress may derive from the placenta's mitochondrial mass, which increases with gestational age (Wang and Walsh 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first trimester of pregnancy, the formation and development of placental blood flow results in a rapid increase in partial oxygen pressure (1,2). Increased metabolic activity and reduced antioxidative activity in uncomplicated pregnancy may lead to exaggerated oxidative stress (OS) (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%